ANKRD36 Is Involved in Hypertension by Altering Expression of ENaC Genes. Issue 11 (7th October 2021) - Yan, Yupeng; Wang, Jin'e; Yu, Liang; Cui, Bing; Wang, Hongrui; Xiao, Xiao; Zhang, Yu; Zheng, Jun; Wang, Jingjun; Hui, Rutai; Wang, Yibo
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Hypertension is the most important risk factor for cardiovascular and cerebrovascular diseases. Getting deep insight into the pathogenesis of hypertension is necessary. Objective: To investigate the role of ANK (ankyrin) repeat domain 36 ( ANKRD36 ) in hypertension. Methods and Results: We first recruited an essential hypertension cohort and then performed genome-wide transcriptome analysis with peripheral blood mRNA. ANKRD36 was found to be significantly lower expressed in hypertension. The anchorin repeat domain mediates a variety of protein-protein interactions. The ENaC (epithelial sodium channel) genes expression was found upregulated in human umbilical vein endothelial cells with ANKRD36 knockdown by using Affymetrix expression profile chip. In human embryonic kidney epithelial cells and HEK293T (human embryonic kidney cells), ANKRD36 overexpression significantly downregulated expression of ENaC genes, and ANKRD36 knockdown upregulated their expression. The chromosome immunoprecipitation assay and yin yang 1 ( YY1 ) knockdown showed the expression of ENaC was regulated by ANKRD36 via YY1, a dual-function transcription factor ubiquitously expressed in human tissues. Immunocoprecipitation and fluorescence resonance energy transfer assay confirmed the interaction between ANKRD36 and YY1. The nucleo-cytoplasmic ratio of YY1 decreased when ANKRD36 was overexpressed and also increased when ANKRD36 was knocked down. ANK2 domain of ANKRD36 was critical to its interaction with YY1. Ankrd36 knockout mice showed higher blood pressure levels and Na + reabsorption, especially when fed with high-salt diet. Higher expression of ENaC genes was observed in renal tubular epithelial cells from the knockout mice, and Yy1 knockdown mitigated the alteration. Ankrd36 knockout mice also showed more sensitive response to ENaC inhibitor amiloride treatment. Conclusions: We identified that ANKRD36 was involved in blood pressure regulation by interacting with YY1 and then altering expression of ENaC genes. Lower expressed ANKRD36 in hypertension might be a potential therapeutic target, and the application of ENaC inhibitors on hypertension treatment might be extended when serum K + levels are closely monitored.